Fault identification in HVDC grids using a transient parametric model. Issue 2 (2020) - Verrax, Paul; Bertinato, Alberto; Kieffer, Michel; Raison, Bertrand
Abstract: This paper presents a novel single-ended fault identification algorithm for meshed High Voltage Direct Current grids. This algorithm can be used in the context of fully-selective fault-clearing strategies. Once a fault is suspected, using a parametric model describing the voltage and current evolution just after the fault occurrence, a maximum-likelihood estimate of the fault distance and impedance is evaluated. The presence of the fault is then confirmed depending on the size of the confidence region of the obtained estimate. The approach is evaluated on a simulated three-node meshed grid. The current and voltage need to be observed during less than 0.2 ms to get an accurate estimate of the fault characteristics and to identify consistently the faulty line.